Assessing the viability of estimating baleen whale abundance from tourist vessels - Henderson, Angus Fleetwood; Hindell, Mark Andrew; Wotherspoon, Simon; Biuw, Martin; Lea, Mary-Anne; Kelly, Nat; Lowther, Andrew Damon (Frontiers in Marine Science, 2023)
As Southern hemisphere baleen whales recover, they are again becoming dominant consumers in the Southern Ocean. Key to understanding the present and future role of baleen whales in Southern Ocean ecosystems is determining their abundance on foraging grounds. Distance sampling is the standard method for estimating baleen whale abundance but requires specific logistic requirements which are rarely achieved in the remote Southern Ocean. We explore the potential use of tourist vessel-based sampling, as a cost-effective solution for conducting distance sampling surveys for baleen whales. We aimed to determine if tourist vessel-based surveys could be effective in determining baleen whale abundance in the southwest Atlantic sector of the Southern Ocean. We did this in two parts. First, we used tourist vessel tracks to estimate the likely whale sightings per tourist's vessel voyage to understand how many voyages are needed to meet the model requirements. Second, we simulated the abundance and distributions of four baleen whale species for the study area and sampled them with both non-standardized tourist vessel-based surveys and standardized line transect surveys. Data were modeled using a generalized additive model and results were compared to the original simulated baleen whale abundance and distributions. We show that for the southwest Atlantic, 12-22 tourist voyages are likely required to provide an adequate number of sightings to estimate abundance for humpback and fin whales, and relative estimates for blue, sei, Antarctic minke, and southern right whales. Our analysis suggests tourist vessel-based surveys are a viable method for estimating baleen whale abundance in remote regions.